Rainfall-induced Failures of Residual Soil Slopes with Spatial Variability of Hydraulic Conductivity - Suradi, Muhamad (INTEK: Jurnal Penelitian, 2016)
The aim of this paper was to examine the effect of spatial variability of hydraulic conductivity, commonly existing in nature, on rainfall-induced failures of residual soil slopes. Parametric study was carried out at typically residual soil slopes with two distinctively different types of hydraulic conductivity, high (ks=10-4 m/s) and low (ks=10-6 m/s) conductivity, in Singapore. Finite element method was applied in this slope stability analysis using commercial SVFlux and SVSlope software in a couple manner. Rainfall intensity was varied as a fraction of the hydraulic conductivity. As a result, greater spatial variability of saturated hydraulic conductivity affects more noticeably the instability of both high and low-conductivity soil slopes exposed to high-rainfall intensity (I > 0.05 ks for high-conductivity slopes and I >1 ks for low- conductivity slopes). However, there was a negligible effect of spatial variability of hydraulic conductivity on the instability of slopes subjected to low-rainfall intensity, even this spatial variability tended to slightly increase the stability of high-conductivity slopes.